The cancer multi-disciplinary team from the co-ordinators' perspective: results from a national survey in the UK - Jalil Rozh; Lamb Benjamin; Russ Stephanie; Sevdalis Nick; Green James SA (BMC, 2012)
Abstract Background The MDT-Coordinators' role is relatively new, and as such it is evolving. What is apparent is that the coordinator's work is pivotal to the effectiveness and efficiency of an MDT. This study aimed to assess the views and needs of MDT-coordinators. Methods Views of MDT-coordinators were evaluated through an online survey that covered their current practice and role, MDT chairing, opinions on how to improve MDT meetings, and coordinators' educational/training needs. Results 265 coordinators responded to the survey. More than one third of the respondents felt that the job plan does not reflect their actual duties. It was reported that medical members of the MDT always contribute to case discussions. 66.9% of the respondents reported that the MDTs are chaired by Surgeons. The majority reported having training on data management and IT skills but more than 50% reported that they felt further training is needed in areas of Oncology, Anatomy and physiology, audit and research, peer-review, and leadership skills. Conclusions MDT-Coordinators' role is central to the care of cancer patients. The study reveals areas of training requirements that remain unmet. Improving the resources and training available to MDT-coordinators can give them an opportunity to develop the required additional skills and contribute to improved MDT performance and ultimately cancer care. Finally, this study looks forward to the impact of the recent launch of a new e-learning training programme for MDT coordinators and discusses implications for future research.